Synthesis of piperidine natural products by allenic cyclisation - Lim, Chia Juan (2013)
The various strategies for the synthesis of Nuphar alkaloids that have been reported to date are reviewed. Earlier applications of silver catalysed cyclisation of allenic hydroxylamines are discussed. The synthesis of four Nuphar alkaloids using allenic hydroxylamine cyclisation is discussed. The allenic alcohol precursor is obtained in optically active form using an enzymatic resolution procedure, optimised by DOE methods. The cyclisation reaction is found to be highly dependant on the specific silver salt employed and also on the presence of moisture. The side chains required for the unnamed Nuphar indolizidine and Nupharamine are introduced by cross metathesis. The side chain for (-)-deoxynupharidine and Castoramine are introduced by cross metathesis, followed by a subsequent stereoselective alkylation. The previous synthesis of Cernuine is discussed. Prelimary studies for the formation of 1,3-diamines via N-N tethered allenic cyclisation or Michael addition are discussed. A potential precursor for the preparation of the 1,3-diamine moiety in the total synthesis of Cernuine using Denmark’s carbonylation and Feringa’s methylation is described.